STUDY OF TOTAL SUSPENDED MATTER DISTRIBUTION USING SATELLITE DATA AND NUMERICAL SIMULATION IN PORONG SIDOARJO, EAST JAVA - -, Herman; Osawa, Takahiro; Arthana, I W (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 1, 2012)
Sedimentation is one of coastal dynamic processes. Sedimentation in the mud volcano of Porong at Sidoarjo is an important phenomena to be known as a reference to find out a good solution in the tragedy of mud volcano eruption. Observation of the sedimentation process in the mud volcano eruption of Porong Sidoarjo needs in situ data and data processing technique to know of more details about sedimentation process and the main cause of the sedimentation and the large mud volcano eruption. Therefore, studying of sedimentation process needs the quick timing and high accuracy method. One of the technique which can be used is remote sensing method compared with numerical model and in situ data oservation. Study area is in the Regency of Porong Sidoarjo Province of East Java on August 2008 in position of 7°30’ S - 7°40’ S and 112° 30’ E - 113°30’ E. The aim of this study is to know the pattern of TSM distribution from satellite image using the algorithm which was introduced by Zhou and Kutser. The pattern of TSM from the Landsat and Modis satellite images show that the TSM distribution from the porong river, will then accumulate to the estuary. But, the concentration will decrease in the area that is far from the estuary. This is caused by the influence of the tide current in the Madura strait. From the simulation model was shown that the sediment distribution is influenced by pattern of current generated by tide. High tide where the current move to the upstream sediment in the porong estuary, the sediment was then accumulated in the estuary area. However, at low tide where the current move to the downstream, sediment transportation will move out from the estuary at the maximum level. The pattern of current shows that the moving is to the south direction in the porong coastal that will cause the sediment concentration that out from the porong estuary willgo to to the south direction. The water flow in front of the mouth of porong estuary maybe one of the cause why the sediment distribution tend to move to the south direction.
Keywords: Sediment, Remote Sensing, Model Simulation